2014
DOI: 10.1371/journal.pone.0113910
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Endothelial Cells with High Aldehyde Dehydrogenase Activity and a Highly Angiogenic Phenotype

Abstract: Tumor blood vessels play an important role in tumor progression and metastasis. It has been reported that tumor endothelial cells (TECs) exhibit highly angiogenic phenotypes compared with those of normal endothelial cells (NECs). TECs show higher proliferative and migratory abilities than those NECs, together with upregulation of vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2). Furthermore, compared with NECs, stem cell markers such as Sca-1, CD90, and multidrug resistance 1 are upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 25 publications
3
57
0
Order By: Relevance
“…(22) We previously reported that TEC expressed higher ALDH levels compared with NEC. (17) Consistent with the previous report, ALDH mRNA expression levels in TEC were significantly higher than those in NEC (Fig. 1a).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…(22) We previously reported that TEC expressed higher ALDH levels compared with NEC. (17) Consistent with the previous report, ALDH mRNA expression levels in TEC were significantly higher than those in NEC (Fig. 1a).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, HM‐TEC showed a more stem cell‐like phenotype and a more resistant profile to anticancer drugs (paclitaxel) with ATP‐binding cassette subfamily B member 1 (ABCB1) upregulation compared with LM‐TEC. In our previous study, no difference in ABCB1 expression levels was observed between ALDH high and ALDH low TEC and, therefore, ABCB1 and ALDH may have mutually exclusive roles in drug resistance development.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations